Lebensweise des Fischadlers - Beutefang und Jungenfütterung - Möller, Wilhelm; Möller, Peter (IWF (Göttingen), 1981)
Pandion haliaëtus, Brut- und Nahrungsgebiet des Fischadlers, Jagdflug, Erbeuten einer Forelle, Beutetransport (Männchen) zum Horst, Verfüttern (Weibchen) von Fischen an die Nestlinge, Ausfliegen der Jungen. Mit Zeitdehnung. : Pandion haliaëtus: brood and feeding territory of the osprey; hunting flight; capture of a trout; the male carrying the prey to the eyrie; the female feeding the young with fish; the young leaving the nest. With slow-motion.